Lonicerae Japonicae Caulis: a review of its research progress of active metabolites and pharmacological effects - Cao, Yu-Xia; Ji, Peng; Wu, Fan-Lin; Dong, Jia-Qi; Li, Chen-Chen; Ma, Ting; Yang, Hao-Chi; Wei, Yan-Ming; Hua, Yong-Li (Frontiers in Pharmacology, 2023)
Lonicerae Japonicae Caulis is the aboveground stem part of the Lonicera Japonica Thunb, which belongs to the medicine food homology species in China. It has the effects of clearing away heat, toxic material, dredging wind and unblocking collaterals. Modern research shows that it contains various active metaboliteingredients and a wide range of pharmacological effects, which is of great research and clinical application value. It mainly contains organic acids, volatile oils, flavonoids, triterpenes, triterpene saponins and other active metaboliteingredients. Its pharmacological effects mainly include anti-inflammatory, antibacterial, antitumor, antioxidant, and repairing bone and soft tissue. Based on the literature reports in recent years, the active metaboliteingredients, pharmacological effects and mechanisms of Lonicerae Japonicae Caulis were sorted out and summarized. It lays a foundation for explaining the efficacy and material basis and application value of Lonicerae Japonicae Caulis. And iIt aims to provide a reference for the in-depth research, development and utilization of Lonicerae Japonicae Caulis.